Exploring Female EFL Teachers’ Professional Agency for Their Sustainable Career Development in China: A Self-Discrepancy Theory Perspective - Ruan, Xiaolei; Toom, Auli (Frontiers in Psychology, 2022)
A large and growing body of literature has investigated teacher agency in the realm of general education. However, far too little attention has been paid to EFL teachers’, especially, female EFL teachers’ professional agency for their career development in the Chinese higher education setting. To address this gap, this study explores female EFL teachers’ professional agency from a self-discrepancy theory perspective, namely, how the participant teachers have perceived discrepancies in their professional development and how they have enacted their professional agency to realize sustainable development. Based on a metaphor investigation of 167 teachers and interview with 9 of them, the current study found: 1) there are certain discrepancies between female EFL teachers’ self-guides and actual self concerning their professional identity construction; 2) female EFL teachers’ professional agency is manifested in the continuum of iteration, practical-evaluation, and projectivity processes, as well as in the entity of personal and environmental factors; 3) female EFL teachers’ professional agency and gender identity are closely intertwined with each other. This study can offer implications for teacher agency research and female teachers’ sustainable development at large.